Why the Wetlands of Puerto Viejo did loses its legal protection: analyzing the motives - Ramirez, Dámaso W. (2018)
Puerto Viejo wetlands is a coastal marine ecosystem southern of Lima. Since 2008, this wetlands was protected by the Peruvian State and declared a Wetland Reserved Zone of Puerto Viejo, a transitory category provided by SINANPE (Sistema Nacional de Áreas Naturales Protegidas por el Estado). In April 2017, a Ministerial Resolution did reversal [desafectación] the transitory protection of Puerto Viejo Wetlands, losing the category of Reserved Zone and being legally unprotected. The present work analyzes and discusses the technical criteria for the reversal (representativeness, efficiency, consistency, connectivity, equilibrium, complementarity and external coherence) that were applied to Puerto Viejo Wetland.